Masa-Depan Cerah, Bahaya Menunggu: Negara-Bangsa Baru dan Kekerasan Massal di Asia Tenggara - Henk Schulte Nordholt (Universitas Gadjah Mada, 2014)
In this article the impact of the Cold War in Southeast Asia is evaluated. The region was turned into the hottest battlefields of this conflict which costed the lives of about seven million people. The Cold War also terminated fragile attempts to turn newly independent nation-states into democracies. Instead every country in Southeast Asia experienced authoritarian rule by either capitalist of socialist regimes. In the capitalist countries middle classes emerged which profited from economic growth under authoritarian rule. Since democracy was associated with instability and mass violence and economic growth with authoritarian rule, middle classes were very late in supporting new attempts to democratize their political systems.